2012
DOI: 10.1111/and.12051
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index has no impact on sperm quality but on reproductive hormones levels

Abstract: The influence of overweight and obesity on sperm quality and reproductive hormone levels is under discussion. The aim of the present retrospective study was to evaluate the influence of body mass index (BMI) on sperm quality and reproductive hormones. We analysed semen samples and serum levels of FSH, LH, T and PRL of a total of 2110 men attending our andrology unit from 1994 to 2010 due to infertility work-up. Patients were stratified according to their BMI in four groups. Main outcome measures were sperm mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
2
17
0
2
Order By: Relevance
“…They also contradict the recent meta-analysis (5), but it can be noted that those authors found a negative relationship for T, SHBG, and free T (21,22) with increased BMI, which may, at least in part, explain our findings. Similar findings were reported by Al-Ali et al (23), with no influence on all assessed sperm quality parameters, but on LH (P¼ .001), T (P< .001), and PRL (P¼ .044). In a cohort of Danish men, serum T, SHBG, and inhibin B all decreased with increasing BMI, whereas free androgen index and E 2 increased with increasing BMI.…”
Section: Discussionsupporting
confidence: 89%
“…They also contradict the recent meta-analysis (5), but it can be noted that those authors found a negative relationship for T, SHBG, and free T (21,22) with increased BMI, which may, at least in part, explain our findings. Similar findings were reported by Al-Ali et al (23), with no influence on all assessed sperm quality parameters, but on LH (P¼ .001), T (P< .001), and PRL (P¼ .044). In a cohort of Danish men, serum T, SHBG, and inhibin B all decreased with increasing BMI, whereas free androgen index and E 2 increased with increasing BMI.…”
Section: Discussionsupporting
confidence: 89%
“…It should be emphasized our protocol was based only on exercise so that it may facilitate participants´ compliance with the intervention. These findings are of particular interest given that abdominal obesity has a negative impact on reproductive hormone levels such as testosterone (17). In a more detailed way, current evidence suggests excess adipose tissue results in increased conversion of testosterone to estradiol, which may lead to secondary hypogonadism through reproductive axis suppression (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five studies met the inclusion criteria, but five did not pass critical appraisal due to shortcomings in their statistical analysis or reporting (Al-Ali et al, 2012Jamshidi, 2011;Relwani et al, 2011;Sekhavat and Moein, 2010) (Figure 1 Supplementary Table S1). The overall quality of included studies ranged from 4/9 to 8/9.…”
Section: Study Characteristicsmentioning
confidence: 99%